Frontline Science: Placenta‐derived decidual stromal cells alter IL‐2R expression and signaling in alloantigen‐activated T cells. Issue 3 (20th September 2016) - Erkers, Tom; Solders, Martin; Verleng, Lotte; Bergström, Cecilia; Stikvoort, Arwen; Rane, Lalit; Nava, Silvia; Ringdén, Olle; Kaipe, Helen
Abstract : Decidual stromal cells increase concentrations of IL‐2 in the allogeneic setting, and reduce the IL‐2 receptor expression and signaling in T cells. Abstract : This study investigated how stromal cells affect the IL‐2 pathway in alloantigen‐activated T cells. We found that decidual stromal cells (DSCs) from term placentas promoted a high production of IL‐2 in cultures with alloantigen‐activated T cells. The intensity of expression of cluster of differentiation 25 (CD25; IL‐2Rα) on T cells was increased by DSCs, whereas the frequency and intensity of expression of the signaling subunits CD122 (IL‐2Rβ) and CD132 (IL‐2Rγc ) were reduced. Consequently, uptake of IL‐2 and STAT5 phosphorylation (pSTAT5) was abrogated. DSCs also decreased the proportion of pSTAT5 + T cells in response to IL‐15, which also use CD122 for signaling. Addition of DSCs to the allogeneic cultures did not increase the expression of programmed death 1 (PD‐1) or CD95, indicating that they did not promote T cell exhaustion. However, exogenous recombinant (r)IL‐2 in similar concentrations in the same setting increased the expression of CD95 and down‐regulated CD122 in T cells. The antiproliferative effect of sirolimus (SRL) and cyclosporine A (CsA), which target the IL‐2 signaling pathway, was diminished by DSCs in vitro. To conclude, DSCs affect IL‐2 production and IL‐2R expression and signaling, which may contribute to the stromal cell‐mediated immune modulation and phenotype shift seen in activated T cells. Altered proliferation in cultures when combining DSCs and SRL or CsA may be of clinical importance, as stromal cells are used in trials for acute inflammation and are often used in combination with conventional immunosuppressive therapies.